Supporting Inclusivity Through an Automatic Transcription Application to Improve Hearing Skills for the Deaf - Apriyanto, Apriyanto; Intes, Amina; Hanim, Saidatul; Alhamdani, Abdul Kodir; Yahya, Sitti Rachmawati (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Inclusivity is the principle that underlies a just and equal society for all individuals, including students or pupils who have hearing disabilities such as the deaf. In an effort to realize inclusivity, technological developments have opened the door to solutions that can improve the quality of life for deaf users. One of the main challenges faced by deaf users is difficulty in understanding and communicating with the outside world through hearing. This article discusses how automatic transcription applications can serve as powerful tools in supporting inclusiveness by improving the listening skills of deaf users. An automatic transcription application is software that is capable of converting spoken conversations into text in real-time. This has the potential to enable deaf users to access previously difficult-to-reach information. The use of automatic transcription applications can provide significant benefits for deaf users. Firstly, it allows pupils and students to follow conversations and presentations better, improving their listening skills. Second, users can participate more actively in various social and educational activities, feeling more confident in interacting with friends, colleagues and instructors. Apart from that, the use of this application can also help in the development of their spoken language, because students can view the transcribed text while listening to the conversation. However, there are several challenges that need to be overcome in implementing this automatic transcription application. These include accuracy of transcription, availability of appropriate hardware and software, and community understanding of the needs and rights of deaf users. Therefore, collaboration between technology developers, the deaf community, and other interested parties is important in ensuring that automated transcription applications can be used effectively to increase inclusivity for deaf users.